Pelatihan Penulisan Instrumen Psikologi sebagai Dasar Penelitian Guru di SMP Negeri 3 Patalassang Kabupaten Gowa - Sulaiman, Dwi Rezky Anandari; Shabrina Syntha Dewi; Ninik Rahayu Ashadi; Abdal, Nurul Mukhlisa; Wirawan Setialaksana; Irwansyah Suwahyu; Muhammad Asriadi (Jurnal Hasil-Hasil Pengabdian dan Pemberdayaan Masyarakat, 2023)
The Psychological Instrument Writing Training for Research Foundation aims to increase the understanding and interest of teachers at SMP Negeri 3 Patalassang in conducting psychological research and being able to publish it in journals. Psychological research can help teachers become more effective in teaching and help students achieve their learning potential. The problems faced by teachers at SMP Negeri 3 Patalassang are (1) limited information on how to conduct psychological research, and (2) the need for guidance from competent parties in developing psychological variable instrument. The solution offered is to provide material on writing psychological instruments as a research foundation. The speaker provides material that suits the problems in the partner school, but also motivates teachers to develop the great potential that the school and teachers have. The implementation stage consists of two stages. The first stage is divided into two sessions, the first session is about delivering research materials and psychological variable instruments. The second session is a question and answer session. The second stage is the training session for developing psychological variable instruments. The training method used is through lecture, discussion, and simulation.